Information Quality, Service System Quality on repurchase intention with Shopee application user satisfaction - Anjani Mutiara Azkia; Mega Dewi; Khairudin Khairudin (Islamic Accounting Journal, 2022)
In the current era of globalization, business competition is growing rapidly. Over time, business development plays a very important role in aspects of human life activities. Currently in Indonesia, there is a fast growing business, namely businesse-commerce. E-commerce is a commercial transaction using Internet media and devices that are integrated with the Internet between organizations and individuals. The continued growth of e-commerce in Indonesia has enabled buyers to enliven the industry. Shopee is a market-based mobile application and is said to be the first mobile market application available to consumers. Shopee is an online shopping platform application that focuses more on mobile platforms, so that people can more easily find, shop and sell products directly on their cellphones. This study aims to determine and analyze "The Effect of Information Quality, System Quality and Service Quality on Shopee Application User Satisfaction". This study uses a descriptive qualitative research method. Sampling was carried out by using a non-probability sampling method, purporsive sampling, with a total sample size of 100 people. The data analysis technique used is descriptive analysis and multiple linear regression analysis. Based on the results of descriptive analysis, it shows that the variables of information quality (X1), system quality (X2), service quality (X3) and user satisfaction (Y) are in the good category. The results of multiple linear regression analysis can be concluded that information quality (X1), system quality (X2) and service quality (X3) have a positive and significant effect on user satisfaction (Y) both partially and simultaneously.Keywords: E-commerce, Information Quality, System Quality, Service Quality, User Satisfaction